Dynamics of the physical properties and the fiber fractioning of the meal of dolic integral forage (Lablab purpureus), biotransformed with Trichoderma viride for feeding monogastrics - Sav?n, Lourdes; Vali?o, Elaine; Bell, Ren?; Hern?ndez, Yasmila (Cuban Journal of Agricultural Science, 2014)
The dynamics of the physical properties and the fiber fractioning of the meal of integral forage of Lablab purpureus, innoculated with M5-2 and 137 MCX-1 strains of the lignocellulitic fugus Trichoderma viride, was studied. The objective of this study was to evaluate the nutritional quality of the fibrous fraction of the meals submitted to a solid state fermentation (SSF). Fifty grams of the substratum were used to determine the indicators of fiber fractioning (neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin, hemicellulose and cellulose), as well as the physical properties: volume, solubility, and water adsorption ability (WAC) at 0, 48, 72, 96 and 120 h after the inoculation. A split plot was carried out in order to study the measuring. There was a significant interaction treatment x time of sampling (P < 0.001) for NDF, ADF, cellulose, hemicellulose, solubility and volume. There was a decrease of the NDF (P < 0.001) from the integral meal inoculated at 24 and 48 h with the 137MCX-1 and M5-2 strains, respectively. The highest decrease of NDF (8.3 percentage units), inoculated with the M5-2 strain, was obtained at 72h. This coincided with the highest increase (P < 0.001) of cellulose and the decrease of hemicellulose, from 23.37 to 19.15 %. There was low content of lignin (P < 0.001), regardless of the strains, at 72 h. The results indicated an increase of the nutritional quality of the fibrous fraction for the meal of dolicho integral forage, inoculated with both strains. This makes possible the consideration of its inclusion as an alternative food for monogastric species. Key words: nutritional quality, fiber fraction, Trichoderma viride, integral forage meal, Lablab purpureus.